التصميم بمساعدة الحاسوب ونمذجة نظام تسخين المياه المنزلية بالطاقة الشمسية مع كفاءات مختلفة للاقط الشمسي وحجوم مختلفة لحوض التخزين - كفا, سمير; ياخور, يوسف (Latakia University Journal -Engineering Sciences Series, 2019)
يبين هذا البحث نمذجة السخان الشمسي للمياه المنزلية، ومحاكاته الديناميكية. أنجزت المحاكاة على أساس سنوي لنظام شمسي يعمل في مدينة اللاذقية بسورية , وهو يؤمن الماء الساخن لأسرة مؤلفة من أربعة أشخاص، و يتألف من لاقط شمسي مسطح , حوض تخزين الماء , منبع طاقة مساعد و جهاز لخلط الماء . استخدم الموديل الرياضي لتقويم التغير السنوي لنسبة التغطية الشمسية وفقاً أو تبعاً لحجم حوض التخزين , درجة حرارة الماء الساخن المطلوبة, الفارق بين هذه الدرجة، ودرجة حرارة المياه في حوض التخزين وبشكل عام الطلب المنزلي على الماء الساخن . أظهرت النتائج لعدد من التصاميم المختلفة ذات أحجام أحواض تخزين مختلفة بأن الأنظمة ذات الحجم الكبير تنتج قيماً أكبر لنسبة التغطية الشمسية. على كل حال، عندما يستخدم حوض تخزين كبير، فإن نسبة التغطية الشمسية تكون أقل تأثراً بتغير بارمترات التشغيل الأخرى. يمكن أن تستخدم نتائج المحاكاة لتصميم نظام لاقط شمسي . This paper shows the modeling and dynamic simulation, of a domestic solar water heating installation. The results of simulations performed on an annual basis for a solar system, operated in Lattakia (Syria), which provides hot water for family (four persons) are presented. The installation consists of a solar flat collector, a water storage tank, a source of auxiliary energy, and a device for blending water. The mathematical model is used to evaluate the annual variation of the solar fraction respect to the volume of the storage tank, demand hot water temperature according, difference of this temperature and preset storage tank water temperature, and consumption profile of the domestic hot water demand. The results for a number of designs with different storage tank volumes show that the systems with greater volume yield higher solar fraction values. However, when a larger storage tank volume is used, the solar fraction is less sensitive to a variation of these operation parameters. The results of this simulation may be used to design a solar collector system.